Zwolennik Bourgeta. Stefan Żeromski i psychologia powieści - Jauksz, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article presents young Żeromski’s fascination with the writings of Paul Bourget. Basing on the Polish writer’s journal entries concerned with Une crime d’amour and Mensonges one can trace an ambivalent attitude towards those psychological novels developed in the late 1880s. By young Żeromski’s standards Bourget falls behind other masters of prose he admires at the time, namely Turgenev and Dostoyevsky. Still, despite Bourget’s didacticism, the aspiring youth cannot refrain from fascination for the descriptions of characters, whose emotions so often so clearly mirror his own. There are at least a few plots (an aspiring writer’s ambitions in the great world, the memory of a love lost etc.) which could have caught Żeromski’s attention as valid attempts to capture experiences known to him as well. It is therefore the identification process that stands in the way of condemning the moralistic ambitions of Bourget and allows the French writer’s works to remain an important point of reference for the Polish witer’s upcoming writing endeavors.